2019
DOI: 10.2174/0929867324666171006131927
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Naphthoquinones and Furano-naphthoquinones as Antiinvasive Agents

Abstract: Cancer is a leading cause of mortality in the world and metastasis is to blame. Invasion is the initial step of metastasis. Therapies targeting epithelial-mesenchymal transition (EMT), cancer stem cells (CSCs) and signal transducer and activator of transcription 3 (STAT3) signaling pathways can reduce stemness of cancer cells and thus inhibit cancer invasion. A large number of anti-cancer naphthoquinones (NQs) can target cancer invasion by acting on EMT, CSCs and STAT3 signaling. Furano-naphthoquinones (FNQs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…24,25 In the family of quinones, 1.4-naphthoquinones are the most important, as their derivatives exhibit a wide variety of biological properties, 26 and some of them (eg, shikonin, plumbagin) have been found to act against invasion and metastasis in a variety of cancers, such as leukemia, breast, colon and lung cancers. 27 In this study, we demonstrated the effects of a natural 1.4-naphthoquinone derivative Ventilagolin on migration, invasion and EMT of human HCC and determined the possible underlying mechanism. We showed that Ventilagolin inhibited the proliferation of HepG2 and SMMC-7721 cells and suppressed HCC tumor growth of nude mice in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…24,25 In the family of quinones, 1.4-naphthoquinones are the most important, as their derivatives exhibit a wide variety of biological properties, 26 and some of them (eg, shikonin, plumbagin) have been found to act against invasion and metastasis in a variety of cancers, such as leukemia, breast, colon and lung cancers. 27 In this study, we demonstrated the effects of a natural 1.4-naphthoquinone derivative Ventilagolin on migration, invasion and EMT of human HCC and determined the possible underlying mechanism. We showed that Ventilagolin inhibited the proliferation of HepG2 and SMMC-7721 cells and suppressed HCC tumor growth of nude mice in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 91%
“… 24 , 25 In the family of quinones, 1.4-naphthoquinones are the most important, as their derivatives exhibit a wide variety of biological properties, 26 and some of them (eg, shikonin, plumbagin) have been found to act against invasion and metastasis in a variety of cancers, such as leukemia, breast, colon and lung cancers. 27 …”
Section: Discussionmentioning
confidence: 99%
“…There are only four classes of USFDA-approved antifungal drugs to treat candidiasis, including the structures of flucytosines, azoles, echinocandins, and polyenes. Naphthofuranquinones are a quinine subclass possessing some bioactivities such as antimicrobial, anti-inflammatory, and antitumor potencies (Tsang et al, 2018). Previous studies (Gershon and Shanks, 1975;Nagata et al, 1998;Neto et al, 2014;Rejiniemon et al, 2014;Hassan et al, 2016;Xie et al, 2016) demonstrated that naphthofuranquinones showed the capability to eradicate Candida species.…”
Section: Introductionmentioning
confidence: 99%
“…Seus efeitos em linhagens celulares de câncer são bastante citados na literatura e, corroborando com nossos estudos, de forma geral apresentam atividade em diversos tipos de câncer como: mama, endométrio, ovário, próstata, cólon, pulmão, pâncreas, esôfago, bexiga, linfoma, fígado (CHANG et al, 2003;DEEP et al, 2016;KIM et al, 1998;LIAW et al, 2002;LIU et al, 2016;QAZI et al, 2018;RIESER et al, 1996;SUN et al, 2014;TORRES et al, 2012;YANG;LEE, 2016;YAP et al, 2017). furano-naftoquinonas, com maior destaque para o lapachol e a β-lapachona (LEE et al, 2015;TSANG et al, 2017). Estudos de citotoxicidade em linhagens de câncer mostraram pouco ou nenhum efeito em relação aos efeitos de extratos de malva.…”
Section: Curva-respostaunclassified